Insentif Pajak Penghasilan Final UMKM Ditanggung Pemerintah Di Masa Pandemi Covid-19 - Kemas Fahmi Hamzah; Budiasih Widiastuti (Akuntansiku, 2023)
The purpose of this study is to explore the implementation of the Final Income Tax Government-borne for SMEs incentives, socialization strategies, and obstacles during its implementation at KPP Pratama Palembang Ilir Barat. The research method used is qualitative with exploratory studies. Data collection is carried out using library and field research methods in the form of interviews. The steps taken start from data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that presenting the Final Income Tax Government-borne for SMEs incentives at KPP Pratama Palembang Ilir Barat is in accordance with the relevant laws and regulations. In increasing the participation of taxpayers in this program, the socialization strategies carried out are holding tax webinars, conducting tax campaigns on official social media, utilizing employees to participate in campaigns, and conducting tax campaigns using print media. During the implementation of this policy, several obstacles are encountered. These obstacles include: Taxpayers' understanding of tax incentives is still low, obstacles during socialization through webinars, obstacles in reporting realization, and obstacles in the ManDOR application. The novelty of this research is examining the implementation of Regulation No. 23/2018 when tax incentives are given during the COVID-19 pandemic.